Justification for the recognition of a new nominate contract based on project defect management - Greeff, Tanya Nicole (University of Pretoria, 2018)
This research sought to establish whether the general acceptance that the common construction and engineering contracts as falling within the classification of the locatio conductio under South African law is correct. As the classification of a contract attracts specific essentialia and naturalia, and then too certain implied terms one example of an implied term that would have practical relevance is specifically investigated: The warranty against latent defects. Through this example I seek to demonstrate the relevance and importance of establishing what the classification of these contracts is, and its ensuing essentialia and naturalia. The investigation commenced by firstly considering the classification of the common building, construction and engineering contracts, with reference to the South African publications of JBCC and GCC, as well as the internationally published FIDIC Silver Book, FIDIC Yellow Book, and FIDIC Red Book, as well as the NEC ECC Option A and Option B. With alternate dispute resolution mechanisms, such as adjudication and arbitration, resulting in limited publications by way of case law and academic writing on the subject (specifically in South Africa), English law and German law were also consulted. It was established that, unfortunately, the classification of the common building, construction and engineering contracts under South African law is problematic: It does not fit the ordinary and previously accepted classifications, specifically that of the locatio conductio. This makes it questionable whether the warranty against latent defects could be, and should be, implied into any one of these contracts. The recommendation, accordingly, is that it is crucial for the construction and engineering industry to carefully consider and develop the true and relevant essentialia and naturalia applicable to these contracts. Only then will there be certainly as to what may be implied into these contracts, and what will not so be implied. Until this is achieved, the parties to these contracts, in order to have certainty, must deal with aspects such as the warranty against latent defects by way of an explicit written term in the particular contract.
Keywords: Contract; Locatio conductio

Consumer arbitration in South Africa and its effect on the consumer's right to redress and enforcement - Rantsane, Ditaba Petrus (University of Pretoria, 2017)
The thesis entitled "Consumer arbitration in South Africa and its effect on the consumer‘s right to redress and enforcement" notes with concern the outdated and inadequate nature of the Arbitration law currently applied in South Africa. The fact that the Act was enacted in 1965 and has never been amended highlights the desperate need to review the prevailing arbitration law with a view to aligning it with the current needs of the business world. The thesis addresses the concern that consumers are not adequately protected by the current arbitration law and thus substantially develops the discourse on the topic of arbitration in situations of unequal bargaining power. It raises three primary research questions in this context. The first question reads thus, if private arbitration is properly conducted should it still provide the parties with the envisaged benefits? Secondly, is private arbitration constitutional, especially as it impacts upon consumers‘ contracting with large corporations? Thirdly, is the private arbitration process as it is currently applied, constitutional as far as it denies parties an appeal on merits against an award that is clearly wrong? The thesis attempts to answer these questions and offer recommendations for the South African Law Reform Commission (SALRC) within the specific context of commercial arbitration. In addressing these research questions, the thesis incorporates a brief overview followed by a detailed discussion of the Arbitration law framework in South Africa and abroad. The discussion of arbitration abroad is done in order to identify best practices, which could be adapted to suit the South African environment. International Arbitration law receives attention and a few observations regarding how selected foreign jurisdictions treat arbitration. Finally, the thesis explores the possibility of establishing an independent institution that will be fully equipped to handle arbitration proceedings from inception to completion.
Keywords: Consumer arbitration; Consumer rights

The influence of the Consumer Protection Act 68 of 2008 on the common law of sale - Barnard, Jacolien (University of Pretoria, 2013)
The purpose of this thesis is to investigate to what extent the Consumer Protection Act 68 of 2008 (CPA) influences the common law of sale in South Africa. “Common law of sale” refers to the essentialia of sale (the minimum characteristics that parties must have consensus on to conclude a valid sale). The parties must have consensus on the intention to buy and sell, the things sold and the purchase price. The common law of sale also refers to the common law duties of the parties, the duties of the seller in particular (conversely therefore the rights of the buyer). The primary duties of the seller which will be investigated are: a. the duty of safe-keeping (including and investigation into the passing of benefit and risk doctrine); b. the duty of delivery and transfer of ownership; c. the warranty against eviction; and d. the warranty against latent defects. The primary common law duties of the buyer to pay the purchase price and accept the thing sold are included in the investigation as well. The formalities required in certain sale agreements, that wording must be in plain language as well as the buyer’s cooling-off rights are also investigated. An investigation into the influence of the CPA on the common law of sale in South Africa warrants a systematic framework and modus operandi which are: a. an investigation into the historical background of the common law of sale and its principles in the Roman law and Roman-Dutch law; b. a critical analysis of the position where the CPA is not applicable (the common law position); c. an extensive analysis and critical evaluation of the relevant provisions of the CPA and the influence thereof on the common law of sale; d. a comparative analysis of the appropriate provisions in Scotland and Belgium; e. a conclusion of the influence of the CPA on the common law of sale (whether the particular common law of sale principle is confirmed, amended or excluded in terms of the Act); and f. recommendations (taking into account the comparative analysis) regarding the rectification of uncertainties and ambiguities that arose as a result of the investigation. It is also important to remember that the existing principles of the common law of sale will still be applicable for transactions and agreements which fall outside the application of the Act. The golden rule to keep in mind when investigating the influence of the CPA on the common law of sale is to determine which approach and interpretation will be most beneficial to the consumer.
Keywords: Common law of sale; Consumer Protection Act; South Africa